2021
DOI: 10.1186/s42466-021-00145-w
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic encephalomyeloradiculits with multiple autoantibodies against ITPR-1, GFAP and MOG: case report and literature review

Abstract: Background Recently, antibodies against the alpha isoform of the glial-fibrillary-acidic-protein (GFAPα) were identified in a small series of patients with encephalomyelitis. Coexisting autoantibodies (NMDA receptor, GAD65 antibodies) have been described in a few of these patients. We describe a patient with rapidly progressive encephalomyeloradiculitis and a combination of anti-ITPR1, anti-GFAP and anti-MOG antibodies. Case presentation and literature review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Fifty-three relevant studies were identified after title and abstract screening. After reading the full texts and reviewing the references of the retrieved articles, 35 studies were finally included in the qualitative synthesis, of which 14 were retrospective studies [ 11 , 15 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] and 21 were case reports [ 12 , 13 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. A total of 113 patients (46 males and 67 females) were reported to show the coexistence of MOG-IgG and neuronal or glial antibodies in these 35 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-three relevant studies were identified after title and abstract screening. After reading the full texts and reviewing the references of the retrieved articles, 35 studies were finally included in the qualitative synthesis, of which 14 were retrospective studies [ 11 , 15 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] and 21 were case reports [ 12 , 13 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. A total of 113 patients (46 males and 67 females) were reported to show the coexistence of MOG-IgG and neuronal or glial antibodies in these 35 studies.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the cases summarized above, five further patients with ITPR1-IgG/anti-Sj detected only in the CSF have been reported (2 × seronegative [ 29 , 30 ], 2 × no serum available [ 18 ], 1 × no information provided [ 18 ]). However, as all previously published ITPR1-IgG/anti-Sj-positive patients had serum antibodies to ITPR1, and the specificity of the recombinant assays used to detect ITPR1-IgG/anti-Sj has not been formally evaluated for CSF, the clinical significance of this finding is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…However, as all previously published ITPR1-IgG/anti-Sj-positive patients had serum antibodies to ITPR1, and the specificity of the recombinant assays used to detect ITPR1-IgG/anti-Sj has not been formally evaluated for CSF, the clinical significance of this finding is unknown. Moreover, co-existing CSF IgG antibodies to N -methyl d -aspartate receptors (NMDAR) (2×) and glial fibrillary astrocytic protein (GFAP) (3×) [ 16 , 29 , 30 ] were reportedly present in the CSF of some of these patients. CSF GFAP-IgG and CSF NMDAR-IgG can also cause autoimmune encephalomyelitis or encephalitis, respectively, rendering it impossible to attribute these patients’ clinical and paraclinical features to either of these antibodies with sufficient certainty.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MOGAD was perceived primarily as a monophasic CNS inflammatory disease, but further observations showed that a relapsing course occur in 28–60% of patients, and in up to 83% of cases with long-term observation, especially those with persistent positive MOG-IgG status. 99,143 Some evidence of subclinical disease activity and progression has been shown to be present in some of the patients with MOGAD. 2 Patients with anti-NMDAR-EN tend to have more severe neurologic presentations, and poor long-term functional outcomes, and the mortality rate has been reported between 5% and 7%.…”
Section: Discussionmentioning
confidence: 99%